Teaching the Hidden Curriculum - Saper, Kea (TRAILS: Teaching Resources and Innovations Library for Sociology, 2022)
This activity is designed to help students analyze how the hidden curriculum functions in their own educational experiences and the experiences of others. Through this activity, students will be able to define the hidden curriculum, assess their own educational environment, and ultimately, explain how the hidden curriculum contributes to educational inequalities. American universities typically operate on white, middle-class norms, disadvantaging low-income and traditionally underrepresented students who may not be familiar with these. While minoritized students will likely be more implicitly aware of the hidden curriculum, learning about this concept in an academic context will enable these students to concretely understand the educational inequalities in their own experience and develop approaches and strategies to overcome such inequalities. Undergraduate students rely on the cultural capital they have entering college to navigate this environment. Upon entering into college, low-income students must quickly become familiar with the hidden curriculum—a ‘curriculum’ that the dominant student population will already be aware of. In this activity, students will engage in an active learning exercise to define the hidden curriculum, answer questions about their own educational experiences, respond to short essay questions and facilitate a broader class discussion. This activity, including strategized learning goals and assessments, explores the hidden curriculum and resulting educational inequalities, helping students analyze how this concept functions in their own lives.